Thesilenced coercion of voodoo over Nigerian women trafficked from West Africa to Europe - Guia, Maria João (New forms of human trafficking, 2024)
More than one of the most frequent forms of coercion into trafficking in human beings in Nigeria, voodoo is a practice often not so familiar to both academia and practitioners. The way in which victims are introduced into a form of complete psychologic dominance is difficult to understand by the justice officers. Nevertheless, this is a current problem to the European Union, since the identification of several thousands of Nigerian women exploited in prostitution over different Member States, in the last years, obliged justice to understand how this crime is committed under the specific case of voodoo coercion. This chapter provides the reader with an in-depth analysis of how voodoo pushes women into the hands of traffickers and points out the relative inadequacy of control and deterrence measures promoted and financed by the European Union. The externalization of European Union’s border control measures is chosen as the most adequate theoretical framework for this analysis, given the multitude of programs financed by the EU in Nigeria, our case study for THB practices through voodoo coercion.